A psicologia das emergências e dos desastres frente à polidemia de Covid-19: diálogos entre saúde mental, vulnerabilidades, envelhecimentos e sociabilidade online - Pimentel, Pollyana Ludmilla Batista (2021)
The Covid-19 pandemic has become the largest international public health emergency unprecedented in the modern world. In this sense, the general objective of this study was to carry out an analysis of mental health and the use of online social networks by people in maturity and old age, during the emergence of the Covid-19 pandemic, as well as the self-perception of vulnerability in the face of the new coronavirus. Therefore, it starts from the thesis that users of online social networks have better mental health rates than non-users, since these networks work as a facilitator of social interaction, especially in view of the social isolation adopted as a measure to contain the virus . Furthermore, it is believed that people in maturity and old age have a high level of self-perception of vulnerability to the new coronavirus, given the great media impact on the lethality of the disease in this age group, one of the main risk groups. Structurally, this thesis was divided into four distinct studies. The first study was an integrative review of the national scientific literature of the last ten years (2009-2019), aiming to know the national literature on the use of online social networks by Brazilians aged 50 or over. After applying the inclusion and exclusion criteria, two articles were selected. It was found that the scientific production related to the theme is very scarce. The results showed that the main networks used by the participants were: Whatsapp, Facebook, Messenger, Instagram, Snapchat and Linkedln. In addition, it was found that online social networks are an important tool in contributing to a healthy aging process, improving the quality of life of people in the aging process. The second study aimed to understand the social representations of people aged 50 or over about the internet and online social networks. The sample that makes up this study is independent from the sample that makes up study III and IV. 50 people participated, with an average age of 60 years, ranging between 50 and 82 years. Participants answered a sociodemographic questionnaire and the Free Word Association Technique (TALP), having as stimuli: “Internet” and “online social networks”. Using the Iramuteq software, multiple frequency analysis, similarity analysis, as well as prototypical analysis were performed. The results show that the participants' social representations about the internet refer to a means of communication, which helps in the search for information and in the provision of virtual social networks. On the stimulus online social networks, social representations were observed as a source of updating, in addition to being another means of communication. In general, the internet and online social networks are seen by participants as both good and bad simultaneously, demanding care from users. The third study presents an investigation and analysis of the prevalence of common mental disorders and symptoms of anxiety and depression in Brazilians, aged 50 or over, during the Covid-19 pandemic, as well as the self-perceived vulnerability of this population to the new coronavirus . A total of 571 people participated, aged between 50 and 88 years (M=58.83; SD=6.74), with 41.5% (N=237) elderly (over 60 years). The majority (78.5%) were female, with 93.3% claiming to be in quarantine (or social isolation?). As instruments, a sociodemographic questionnaire, the Self-Reporting Questionnaire (SRQ-20), the Hospital Anxiety and Depression Scale (HAD) and the Perception of Social Support Scale (EPSS) were used. All scores showed significant differences regarding the gender of the participants. Women had higher means for anxiety, depression, Common Mental Disorder, and distress. While men have a higher average than women in the Perception of Social Support. It was also observed that adults aged 50 to 59 years, with monthly income less than two minimum wages and those with a greater perception of vulnerability to Covid-19 had a higher prevalence of Common Mental Disorders, anxiety, depression and distress than the elderly. Mental health care is necessary, especially for women, for people with less access to income and for those who feel more vulnerable to the virus. Finally, the fourth study presents an analysis of the impact of the use and non-use of online social networks on the mental health of Brazilians aged 50 years and over during the emergence of the Covid-19 pandemic in Brazil. A total of 571 people participated, aged between 50 and 88 years (M=58.83; SD=6.74), 78.5% of whom were female, with 93.3% claiming to be in quarantine. It is important to emphasize that of the total number of participants, 41.5% (N=237) were elderly (over 60 years old). Regarding the use of online social networks (RSO), 93% of the participants stated that they made use of these tools. Most have been using RSO for over 5 years and remain connected for more than 3 hours a day. The online social networks most used by participants are Whatsapp, Facebook and Instagram. As instruments, a sociodemographic questionnaire, the Self-Reporting Questionnaire (SRQ-20), the Hospital Anxiety and Depression Scale (HAD) and the Perception of Social Support Scale (EPSS) were used. Regarding the scores of anxiety, depression, CMD and Perception of Social Support, there were no differences between people who use OSR and those who do not use OSR. However, when the length of RSO use was moderated by sociodemographic variables, significant differences were found in relation to the participants' gender, age group, income and level of religiosity. Women had higher averages in relation to anxiety and depression, while men had higher averages than women in the Perception of Social Support. It was also observed that adults aged 50 to 59 years, with monthly income less than two minimum wages, had greater psychological damage when compared to the elderly. The importance of using online social networks during the Covid-19 pandemic period is perceived for all participants, especially for the elderly, as more benefits were found for them in terms of mental well-being. Therefore, it is expected that the results of this thesis help in planning psychosocial and health practices, as well as effective public policies for this population.